Amnesty law, political struggles for legitimacy and violence in Mozambique - Igreja, Victor (International journal of transitional justice, 2015)
Two decades after the negotiated peace accord and amnesty law that ended the civil war (1976-1992) between the Frelimo government and the rebel group Renamo, an armed conflict (2013-2014) broke out between Frelimo and Renamo military forces. While in the 1990s the pacification process was locally and internationally celebrated as a successful transition from a socialist, repressive regime and civil war to peace and democratization, the transition process produced different dynamics at the state and societal levels. This article focuses on state and elite politics by analysing debates among Frelimo elites at critical junctures of the peace negotiations with Renamo, the enactment of the amnesty law and subsequent political relations between Frelimo and Renamo. The analysis reveals complex realities that defy mainstream praise for the amnesty law and the allegedly successful peacebuilding in Mozambique. It suggests that Frelimo alone passed the amnesty law to avoid accountability and to imply a public commitment to reconciliation in tandem with their attempt to recover losses incurred in the peace negotiation context. These goals fostered the marked open-endedness of the transition, whereby contested war memories were used as weapons and fierce struggles for political legitimacy involving flashes of political violence occurred well beyond the accord. The article suggests the need for some measure of accountability and a nationwide debate about the composition and role of the security and defence forces in Mozambique.